PENINGKATAN PRODUCTIVITAS DUMP BODY TRUCK MENGGUNAKAN PENDEKATAN LEAN MANUFACTURING Studi Kasus di PT. XYZ - Tangerang - Yunianto Agung Nugroho; Suroso . (Journal Of Communication Education, 2020)
Abstract Resulted in the increasing globalization of the world will be a world mining equipmentneeds to the needs of the growing impact of supporting the production of mining equipment. PT. XYZ isone of the companies supporting the production of mining equipment manufacturers are one of them isthe Body Dump Truck. Body Dump Truck demand in 2013 increased from the previous year 2011 wasonly 120 units per year to 180 units per year. In the effort to deal with the demand, increasedcompetition, cost pressures, the need to improve the performance of their manufacturing operationsoffer the Lean Manufacturing methods, tools, and heuristics to improve the effectiveness and efficiencyin manufacturing.The purpose of this study is to provide the proposed increase in production capacity by identifying andbalancing the work process that occurs in every work process production line must be equal or belowtact time.The results of this study may indicate that the application of the production process of the proposedDump Truck Body can be achieved from the monthly average of 10 units to 18 units. Jig fixture use amethod very effective and efficient production processes, this is evidenced by the decrease cycle time.For each Sub-Assy previously had to be done with the two man power into one man power, and thelead time decreases. It's very good impact for companies to reduce operating costs of production aslow as possible.Keywords: Produktivitas, Lean Manufacturing, Cycle Time, Man Power, Production.